2020
DOI: 10.1097/rti.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax Rate and Diagnostic Adequacy of Computed Tomography–guided Lung Nodule Biopsies Performed With 18 G Versus 20 G Needles

Abstract: Purpose: Conflicting data exist with regard to the effect of needle gauge on outcomes of computed tomography (CT)-guided lung nodule biopsies. The purpose of this study was to compare the complication and diagnostic adequacy rates between 2 needle sizes: 18 G and 20 G in CT-guided lung nodule biopsies. Materials and Methods: This retrospective cohort study examined CT-guided lung biopsies performed between March 2014 and August 2016 with a total of 550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…6,8 However, in a retrospective review of 550 CT-guided lung biopsies comparing 18- and 20-gauge core biopsies, there was no significant difference in sample adequacy (95% and 93%, respectively). 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 However, in a retrospective review of 550 CT-guided lung biopsies comparing 18- and 20-gauge core biopsies, there was no significant difference in sample adequacy (95% and 93%, respectively). 21…”
Section: Discussionmentioning
confidence: 99%
“…6,8 However, in a retrospective review of 550 CT-guided lung biopsies comparing 18-and 20-gauge core biopsies, there was no significant difference in sample adequacy (95% and 93%, respectively). 21 Pneumothorax is well-established as the leading complication of PTNB. However, the reported incidence is widely variable.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for pneumothorax after transthoracic lung biopsy have been examined widely. Among the known risk factors, some are consistent whereas others are inconsistent or even contradictory across published studies, probably owing to various baseline characteristics, biopsy techniques, and analytic methods [8][9][10][11][12]. Although biopsy related pneumothorax frequently occurs during or immediately after procedure, pneumothorax can be identified in the follow-up chest radiographs or even after discharge due to chest pain or dyspnea (delayed pneumothorax) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Positive pressure ventilation and intractable cough are thought to confer a greater risk of systemic air embolism (SAE) and pneumothorax. 8,9 Patients with severe emphysema or interstitial lung disease, and oxygen-dependent patients are also at increased risk of pneumothorax, particularly if the needle trajectory necessitates traversing areas of emphysema [10][11][12] or fibrosis, including blebs, bullae, and honeycombing. Even so, patients with fibrosis, particularly those being assessed for potential lung transplant and with indeterminate nodules, may proceed to PTLB (Fig.…”
Section: Relative Contraindicationsmentioning
confidence: 99%
“…67 A number of factors have been suggested to increase pneumothorax rates. These include patient factors, such as age, 12,68 emphysema, 12,22,48,67 smoking history, 68 and supine 22,68 and lateral decubitus positions 22,67 ; lesion factors, such as small lesion size, 16,[47][48][49]58,67,68 lesion depth, 11,12,[48][49][50]67,68 and subpleural location 47 ; and technique-related factors, such as anterior approach, 67 wider pleural angle, 49 needle gauge or type, 48,67 number of pleural punctures, 12,67,69 and breaching of fissures. 12,22,48,67 A metaanalysis by Huo et al 67 found the highest rate of pneumothorax when traversing bullae or fissures and for patients in the lateral decubitus position (biopsied lung nondependent).…”
Section: Pneumothoraxmentioning
confidence: 99%